Cord Blood SARS-CoV-2 IgG Antibodies and Their Association With Maternal Immunity and Neonatal Outcomes - Addy Cecilia Helguera-Repetto; Isabel Villegas-Mota; Guadalupe Itzel Arredondo-Pulido; Jorge Arturo Cardona-Pérez; Moises León-Juárez; Maria Antonieta Rivera-Rueda; Gabriela Arreola-Ramírez; Paloma Mateu-Rogell; Sandra Acevedo-Gallegos; Gloria Elena López-Navarrete; María Yolotzin Valdespino-Vázquez; Guadalupe Martínez-Salazar; et al. (Frontiers Media S.A., 2022)
Passive transplacental immunity is crucial for neonatal protection from infections. Data on the correlation between neonatal immunity to SARS-CoV-2 and protection from adverse outcomes is scarce. This work aimed to describe neonatal seropositivity in the context of maternal SARS-CoV-2 infection, seropositivity, and neonatal outcomes. This retrospective nested case-control study enrolled high-risk pregnant women with a SARS-CoV-2 RT-PCR positive test who gave birth at the Instituto Nacional de Perinatología in Mexico City and their term neonates. Anti-SARS-CoV-2 IgG antibodies in maternal and cord blood samples were detected using a chemiluminescent assay. In total, 63 mother-neonate dyads (mean gestational age 38.4 weeks) were included. Transplacental transfer of SARS-CoV-2 IgG occurred in 76% of neonates from seropositive mothers. A positive association between maternal IgG levels and Cycle threshold (Ct) values of RT-qPCR test for SARS-CoV-2 with neonatal IgG levels was observed. Regarding neonatal outcomes, most seropositive neonates did not require any mechanical ventilation, and none developed any respiratory morbidity (either in the COVID-19 positive or negative groups) compared to 7 seronegative neonates. Furthermore, the odds of neonatal respiratory morbidity exhibited a tendency to decrease when neonatal IgG levels increase. These results add further evidence suggesting passive IgG transfer importance.